2020
DOI: 10.21203/rs.3.rs-45301/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Detection of Crimean-Congo hemorrhagic fever virus (CCHFV) in Hyalomma ticks collected from Mauritanian livestock

Abstract: Background: Crimean-Congo hemorrhagic fever virus (CCHFV) belongs to the Nairovididae family in the Orthonairovirus genus and is an emerging tick-borne virus. It is endemic in most parts of Africa, Asia, as well as southern Europe, and can cause severe hemorrhagic symptoms in humans with high fatality rates (5-30 %). Methods: Hyalomma ticks were collected from four different livestock herds (cattle and camel) from Mauritania in 2018. The tick species was determined morphologically and confirmed on a molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(49 reference statements)
1
2
0
Order By: Relevance
“…And according to some authors, ticks such as Hyalomma marginatum (Koch, 1844) and Amblyomma variegatum are known to be involved in the distribution of the Crimean-Congo haemorrhagic fever virus [24,25]. Moreover other studies carried out in Ghana [26], in Mali [27] in Mauritania [28] and in Senegal [29] showed prevalences of CCHFV in the three types of ticks identified in this study.…”
Section: Discussionsupporting
confidence: 68%
“…And according to some authors, ticks such as Hyalomma marginatum (Koch, 1844) and Amblyomma variegatum are known to be involved in the distribution of the Crimean-Congo haemorrhagic fever virus [24,25]. Moreover other studies carried out in Ghana [26], in Mali [27] in Mauritania [28] and in Senegal [29] showed prevalences of CCHFV in the three types of ticks identified in this study.…”
Section: Discussionsupporting
confidence: 68%
“…CCHFV Livestock Egypt, Somalia, Tunisia [193] CCHFV Patient Oman [194] CCHFV Cattle, camel H. rufipes, H. dromedarii, H. impeltatum Mauritania [195] CCHFV Camel H. dromedarii United Arab Emirates [196] ALKV Patients Saudi Arabia [197] ALKV Patients [198] ALKV Patient, dead camel Saudi Arabia [197,199] ALKV This virus is a recently described member of the tick-borne hemorrhagic fever group of the genus Flavivirus. Camels and sheep are thought to be the natural hosts of ALKV [202].…”
Section: Pathogens Host Species Tick Vectors Locality Referencesmentioning
confidence: 99%
“…In 2003, there was an urban outbreak of CCHF in which 28.6 % of the cases were fatal ( 41 ). Additionally, CCHFV has also been detected in livestock and ticks in different periods ( 41 , 59 , 63 , 70 ) ( Table 1 ). In Mauritania, 5–49 cases of CCHF have been reported per year ( 73 ).…”
Section: Resultsmentioning
confidence: 99%